A STUDY ON REVIEW OF AIR POLLUTANTS WITH THE IMPACT ON HUMAN HEALTH AND THE CONCEPTUAL DESIGN BASED IMPROVEMENT FOR WELL BEING OF THE SOCIETY - Ganesh Babu Kn 1; Vasanthy Muthunarayanan 2 (Chelonian Research Foundation, 2023)
Studying about the indoor and outdoor air quality status is need of the hour. Air pollutants, such as particulate matter (PM), ozone (O3), nitrogen dioxide (NO2) and sulphur dioxide (SO2) are having the strongest evidence for public health concern. Particulate matter is a major air contaminant in the ambient air and wide information is assessable on its concentrations from various parts of the world. Global Platform on Air Quality and Health has been established to systematically consolidate data on air quality and health by bringing together information on air pollution exposure. Therefore collecting the information and reviews on air pollutants distribution, variation on the season, indoors - out door air pollution analysis with their health impacts and associated studies pave a way to get better acquaintance with air pollution, health and air pollution dilution. In research reviews the existing architecture principles being applied in the developed areas and proposes a solution to the design while keeping in mind that the environment is not harmed. Key words: Indoor and outdoor air quality, Industrial, Residential and sensitive zone buildings, Architectural design solution.